Musées et centres d'art alternatifs pour le jeune public dans l'après 1968 - Carine Brosse (Strenae)
After 1968, three institutions reinvented cultural mediation and museography for young audiences. The CAPC in Bordeaux, the Musée en Herbe, and the Centre Georges Pompidou with its Atelier des Enfants became rare French exceptions offering educational activities for the youth in the 1970s and 1980s. This study aims to show the form and function of these alternative museums and art centers, whose goal is to raise awareness around contemporary art and initiate children into this art realm.